Barn Owls and Black Rats from a Rural Roman Villa at Gatehampton, South Oxfordshire. (3rd September 2021) - Walker, Thomas; Sharpe, Janet Ridout; Williams, Hazel
ABSTRACT: A large assemblage of small mammal and other small vertebrate bones was excavated within a relatively small area of a single room in a Roman villa close to the River Thames in South Oxfordshire. It is argued that these bones are the remains of barn owl pellets and that their presence shows that the roof on this room at least had remained intact for some time after either the entire building or this particular part of it had been abandoned as human habitation. The remains of several juvenile black rats were contained within the assemblage, making this the first record of black rats from a rural Romano-British setting in Oxfordshire and adding to the extremely small corpus of records of this species from a non-urban location anywhere in the country. Radiocarbon dates place the presence of rats and the abandonment of the villa during the second half of the fourth century.